Model Intellectual Capital Sebagai Variabel Moderating Ditinjau Dari Likuiditas, Leverage, dan Profitabilitas Pengaruhnya Terhadap Nilai Perusahaan - Budiningtyas, Dwi Putri; Hutabarat, Zuhri Saputra (Owner : Riset dan Jurnal Akuntansi, 2024)
Using intellectual capital as a moderating variable, this study examines the impact of liquidity, leverage, and profitability on company value. The study examines public banking sector companies listed on the Indonesia Stock Exchange between 2016 and 2021. Secondary data is the data source for this quantitative technique. 39 companies were chosen as samples throughout a six-year period; thus, 234 total data points were evaluated. Multiple regression analysis was performed on the data. The study's findings and data analysis lead to the conclusion that the variables related to profitability and liquidity increase business value. Firm value is significantly and negatively impacted by the leverage variable. The impact of the liquidity and leverage factors on the firm value variable, which is represented by the Tobins'Q index, can be amplified by the intellectual capital variable. The impact of the profitability variable on the company value variable, which is represented by the Tobins'Q index, is mitigated by the intellectual capital variable.